2023
DOI: 10.1101/2023.02.19.23286151
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plasma neurofilament light in behavioural variant frontotemporal dementia compared to mood and psychotic disorders

Abstract: Objective Blood biomarkers of neuronal injury such as neurofilament light (NfL) are being intensively studied to improve diagnosis and treatment of neurodegenerative disorders, but gaps remain in its ability to assist in distinguishing neurodegenerative from primary psychiatric disorders (PPD) with overlapping clinical presentations that commonly cause diagnostic dilemmas. This study aimed to investigate plasma NfL in a range of PPDs, and the diagnostic utility of plasma NfL in differentiating PPD from behavio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…It also is a marker of potential neuronal injury. While some studies have observed increased NfL in schizophrenia and depression 7,8 , recent studies from our group using ultrasensitive technology to measure plasma NfL levels found no evidence of increased NfL in treatment-resistant schizophrenia (TRS) or major depressive disorder (MDD), but a slight increase in individuals with bipolar affective disorder (BPAD) 9,10 . However, these studies did not examine whether age trajectories of NfL in psychiatric disorders differed from those seen in healthy individuals, where higher NfL levels are associated with increasing age 11 .…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…It also is a marker of potential neuronal injury. While some studies have observed increased NfL in schizophrenia and depression 7,8 , recent studies from our group using ultrasensitive technology to measure plasma NfL levels found no evidence of increased NfL in treatment-resistant schizophrenia (TRS) or major depressive disorder (MDD), but a slight increase in individuals with bipolar affective disorder (BPAD) 9,10 . However, these studies did not examine whether age trajectories of NfL in psychiatric disorders differed from those seen in healthy individuals, where higher NfL levels are associated with increasing age 11 .…”
Section: Introductionmentioning
confidence: 87%
“…NfL Z-scores were calculated from age-adjusted percentiles from the large reference cohort (Control Group 2), derived using generalised additive models for location, scale, and shape 9 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation